2012
DOI: 10.1089/scd.2011.0140
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mesenchymal Stem Cells in Perinodular Fat and Skin in Dupuytren's Disease: A Potential Source of Myofibroblasts with Implications for Pathogenesis and Therapy

Abstract: Dupuytren's disease (DD) is a fibroproliferative disorder characterized by aberrant proliferation of myofibroblasts, the source of which remains unknown. Recent studies indicate that circulating and tissue-resident mesenchymal stem cells (MSCs) can differentiate into myofibroblasts. Therefore, the aim of this study was to profile MSCs from phenotypically distinct DD sites including cord, nodule, skin overlying nodule (SON), and perinodular fat (PNF) compared with unaffected internal controls, that is, distant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 53 publications
1
47
1
Order By: Relevance
“…Its lower expression in D cells additionally supports the evidence of accentuated myo�ibroblast phenotype of D cells. Bayat and co-workers [70,71] report similar results. They also detected CD34 and CD90 positive cell populations in cells isolated from the cord and nodule of DD patients.…”
Section: Discussionmentioning
confidence: 55%
“…Its lower expression in D cells additionally supports the evidence of accentuated myo�ibroblast phenotype of D cells. Bayat and co-workers [70,71] report similar results. They also detected CD34 and CD90 positive cell populations in cells isolated from the cord and nodule of DD patients.…”
Section: Discussionmentioning
confidence: 55%
“…However, we and others have shown that at passage 5 the phenotypes of myofibroblasts and normal human dermal fibroblasts tend to merge (30,31). In addition, whereas the cell of origin for Dupuytren's myofibroblasts remains controversial, there is accumulating evidence that the adjacent tissues, including the overlying dermis, make a significant contribution and that these cells are more akin to Dupuytren's myofibroblasts than fibroblasts from carpal tunnel fascia (20). Moreover, Dupuytren's disease is restricted to the palm of the hands in patients with a genetic predisposition.…”
Section: Discussionmentioning
confidence: 84%
“…Recent data suggest that the tissues overlying the Dupuytren's nodules, including the dermis, are likely to constitute a source for myofibroblast precursors during disease progression (20). Therefore, we studied the effect of TGF-β1 on dermal fibroblasts from palmar and nonpalmar skin from patients with Dupuytren's disease, as well as palmar dermal fibroblasts from normal individuals unaffected by Dupuytren's disease.…”
Section: Dermal Fibroblasts Treated With Tgf-β1 Acquire the Myofibrobmentioning
confidence: 99%
“…Many studies were conducted in older populations with at least one analysis group >50 years of age (33)(34)(35)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). The range of symptom duration varied substantially within and across studies.…”
Section: Secondary Screen-quality Assessment Overviewmentioning
confidence: 99%
“…We apply it here to refer to the potentially heterogeneous biomarker associations in populations according to symptom severity or duration, age, gender, and the like. Many of the sufficient-quality studies in this review have been conducted among older patients at the time of surgery (44,45,47,48,50,54,58). Comparatively fewer authors have researched MSD biomarkers in younger subjects with incipient disorders (40,41).…”
Section: Spectrum Effect (Variation Of Biomarkers Across Subgroups)mentioning
confidence: 99%